2014
DOI: 10.1177/1757975913512159
|View full text |Cite
|
Sign up to set email alerts
|

La santé des immigrants au Canada : état des connaissances, interventions et enjeux

Abstract: La population immigrante au CanadaLe Canada accueille annuellement près de 250 000 personnes immigrantes, soit environ 1 % de sa population. En 2011, près de 20.6 % de la population est née à l'extérieur du pays. i Compte tenu du vieillissement de la population et de la chute du taux de natalité, l'immigration constitue une dimension essentielle du marché du travail canadien.La majorité des immigrants sont originaires de l'Asie (58,3 %). Les immigrants en provenance de l'Europe représentent 16 % ; l'Amérique d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Overcoming language barriers in health-care encounters may be a challenge. In countries with culturally and linguistically diverse populations, use of a second language by either the patient or the practitioner is common (32 34). When provision of care in one’s preferred official language is not possible, trained interpreter services are a good alternative (3537).…”
Section: Introductionmentioning
confidence: 99%
“…Overcoming language barriers in health-care encounters may be a challenge. In countries with culturally and linguistically diverse populations, use of a second language by either the patient or the practitioner is common (32 34). When provision of care in one’s preferred official language is not possible, trained interpreter services are a good alternative (3537).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dealing with the administrative challenges of their legal status, people new to Canada also need to work for their livelihood and many have multiple jobs with little free time to devote to their families. Additionally, studies have shown that people new to Canada have low incomes ( Battaglini et al, 2014 ; Creatore et al, 2012 ; Ferzacca, 2012 ; Gravel & Battaglini, 2000 ; Manderson & Smith-Morris, 2010 ), working for arduous and unrewarding jobs ( Martiniello, 1995 ), which is not conducive with a long-term research collaborations despite their goodwill. It might also be expected that patients who were retired would have more availability for long term participation in research, but this is not the case since many patients continue to be involved in social activities or take care of family dependents.…”
Section: Discussionmentioning
confidence: 99%
“…The DAC Network has a Circle of Patient Partners composed of Francophones and people new to Canada. However, few people new to Canada are represented within the patient circles of the DAC Network, yet type 2 diabetes is endemic among them ( Public Health Agency of Canada [PHAC], 2011 ) ( Battaglini et al, 2014 ; Creatore et al, 2012 ; Newbold & Danforth, 2003 ). Although the Network attempts to resolve the low representation of people new to Canada in its research partnerships, it is not clear whether these partnerships are relevant for them or address their expectations which are not always clinical.…”
Section: Introductionmentioning
confidence: 99%
“…Des disparités de santé désavantageant ces populations se perpétuent (Smedley et al, 2003;Tam, 2019); par exemple, les MiRER souffrant d'une maladie ou d'un problème de santé mentale tendent à peu utiliser les services de santé (CSMC, 2019). De plus, la moitié des usagers provenant de minorités ethniques ressentent des insatisfactions envers ces services (Battaglini et al, 2014). Selon une étude d 'Hansen et ses collaborateurs (2006), plus de 50 % des praticiens sondés considèrent « rarement » ou « jamais » les éléments culturels dans leurs diagnostics et décisions cliniques.…”
Section: Diversité Et Accès Aux Services Publicsunclassified